Analysis of the Potential for Increasing Public Green Open Space in Tomohon Tengah District - Afiifa Ayudiah Yasinta; Noortje Marsellianie Benu; Rine Kaunang (Cita konsultindo, 2025)
The availability of Public Green Open Space (RTHP) in an urban area provides beauty, comfort, as a means of education for the community to protect and maintain the ecological stability of the city, as well as a place for people to carry out social and recreational activities. The purpose of this study is to calculate the distribution area of Public Green Open Space and to analyze the potential for increasing Public Green Open Space in Tomohon Tengah District in Tomohon Tengah District. This research was conducted in Tomohon Tengah Sub-district, Tomohon City, with the implementation time of 4 months. The sampling method in this study was purposive sampling which was taken deliberately, in accordance with the required sample requirements. Data analysis methods using Geographic Information System (GIS) using map overlay analysis techniques and descriptive analysis. The results showed that 1) Existing RTHP availability in Central Tomohon District still does not meet the 20% standard, only has an area of 10.33 Ha or 0.68%. 2) Public space characteristics consist of land use, population density, slope and accessibility of distance to the road used to determine potential areas for the provision of green spaces as an effort to increase the availability of green spaces in Central Tomohon District. Most of the Central Tomohon area is “very suitable” and has the potential for the provision of green spaces.